PHILOSOPHEME OF SYMBOL AND CONCEPT OF THE MEANING: PHILOSOPHICAL AND ANTHROPOLOGICAL ASPECTS - P. V. Kretov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2015)
The aim of the study is to find out the meaning of the symbolic nature of the philosophical and anthropological knowledge deployment, as well as symbolic forms of correlation between artificial and natural in the consciousness of human identity and their fixation in the language and also in the forms and structures of culture. The research is based on the methodology of historical and philosophical analysis in synchronic and diachronic aspects, principles of hermeneutic understanding and reconstruction and phenomenological descriptions. Scientific novelty is represented by the postulating such predications of symbolic structures of language and consciousness as multipanorama and transfinite, justification of the ontological status of symbol and symbolism. The symbolic functioning character of language metaphor in scientific discourse and especially the symbolic dimension of semantic field of language and culture, as well as their symbolic association was fixed. The author proves the thesis about the symbolic nature of a holistic, means forming, philosophical knowledge of man, and the relation between the underlying symbolic and metaphorical structures of language and the mechanisms of consciousness, which finds its expression, in particular, in the language of science. The symbolic design that transmits the philosophical aspects of meaning that go beyond definition and formal-logic descriptions is used. In the comparison of the concepts of spiral dynamics, memetics and autopoiesis the existence of a specific symbolic dimension of the semantic field of language, culture and consciousness is postulated. Conclusions of the article define the role of symbol and symbolic and metaphorical constructions and structures of language in forming the discourse of modern philosophical anthropology, which would include the whole thesaurus of language and culture.